Ksharasutra and Ksharakarma in the Management of Common Anorectal Diseases: A Review - Yadav, Praveen K; Pandey, Narayan; Tamrakar, Abhishek (International Research Journal of Ayurveda & Yoga, 2022)
Ksharasutra is a special medicated thread made up of coatings of alkaline ayurvedic drugs on linen thread. Ksharakarma is a procedure in which the kshara is applied over the diseased area for certain time and then it is wiped out. Both the procedures are the boon to ayurvedic surgery. Hemorrhoids, Fistula in ano, Perianal sinus, Pilonidal sinus are the very common anorectal diseases in the present era. Ksharasutra and Ksharakarma are the two vital procedure for the treatment of anorectal diseases which is simple yet efficacious, affordable, ambulatory, with much less recurrence rate and with almost no post-operative complications